1995
DOI: 10.1007/bf02029360
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of the Williams-Beuren syndrome associated with hemizygosity at the elastin locus

Abstract: This study confirms that WBS has a unique clinical picture which can be diagnosed clinically, but also shows that the relative frequency of individual features may have been overemphasized in the past, and that a minority of patients may exist who are clinically indistinguishable from WBS but who appear to have no deletion at 7q11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 12 publications
2
10
0
6
Order By: Relevance
“…Histological examination of the skin in cutis laxa often reveals marked fragmentation or diminution of elastic fibers (6,17,32). This is a considerably different phenotype than that found in SVAS, a pathology arising from elastin mutations that lead to functional hemizygosity (15,16,23,34,35). Skin fibroblast cultures from many cutis laxa patients exhibit reduced ELN mRNA levels or tropoelastin production, but fibroblasts from other affected individuals exhibit normal levels of elastin production with abnormal elastic fiber morphology (17,36).…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination of the skin in cutis laxa often reveals marked fragmentation or diminution of elastic fibers (6,17,32). This is a considerably different phenotype than that found in SVAS, a pathology arising from elastin mutations that lead to functional hemizygosity (15,16,23,34,35). Skin fibroblast cultures from many cutis laxa patients exhibit reduced ELN mRNA levels or tropoelastin production, but fibroblasts from other affected individuals exhibit normal levels of elastin production with abnormal elastic fiber morphology (17,36).…”
Section: Discussionmentioning
confidence: 99%
“…WS is generally sporadic with an incidence of 1/20,000-1/50,000 live births, although familial cases have been reported with appar- [Curren et al, 1993;Morris et al, 1993b;Ewart et al, 1994;Olson et al, 1995;Li et al, 1997;Tassabehji et al, 1997]. Further investigations of SVAS and WS have shown that hemizygosity at the elastin locus occurs in most WS patients Keating, 1994;Borg et al, 1995;Kotzot et al, 1995;Nickerson et al, 1995;Lowery et al, 1995;Mari et al, 1995]. Elastin haploinsufficiency provides an explanation for some of the anomalies found in WS, including SVAS, and a hoarse voice and rapidly aged-appearing skin, which may occur in part because elastin is required for the normal ultrastructure in the vocal ligaments and the skin.…”
mentioning
confidence: 95%
“…Generally, seizures are not associated with WS. Autosomal dominant inheritance has been found in familial WS patients (Sadler et al 1993, almost all patients with WS having hemizygosity at the elastin (ELN) locus and submicroscopic deletions of chromosome 7q11.23 (Ewart et al 1993, Kotzot et al 1995, Nickerson et al 1995. LIM-kinase 1 (LIMK1) and the replication factor C subunit 2 (RFC2), have recently been identified in the deleted chromosomal region of the 3Ј flanking ELN gene (Frangiskakis et al 1996, Tassabehji et al 1996, Osborne et al 1996.…”
Section: Introductionmentioning
confidence: 99%